APPLICATION OF FOURIER TRANSFORM INFRARED SPECTROSCOPY FOR QUALITY CONTROL OF PHARMACEUTICAL PRODUCTS: A REVIEW - Abdul Rahman (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Analysis of pharmaceutical products covers all aspects of quality control of active pharmaceutical ingredients (API) and finished products. Today, Fourier transform infrared (FTIR)spectroscopy, especially in combination with chemometrics software, has emerged as one of the romising analytical techniques to be used in pharmaceutical industry, for quality control of desired pharmaceutical products. Compared with other instrumental techniques, FTIR spectroscopy offers some advantages, namely it is rapid, simple in sample preparation, and not destructive. In this review, the application of FTIR spectroscopy for qualitative and quantitative determinations of API and monitoring drug release are described.Key words: FTIR spectroscopy, quality control, pharmaceutical products.